Diversidade de braconidae (Hymenoptera) e o seu uso como bioindicadores na unidade de conservação Teixeira Soares, Marcelino Ramos, RS - Restello, Rozane Maria (Universidade Federal de São Carlos, 2003)
This work was performed aiming to know Braconidae species from the Conservation Unity of Teixeira Soares, Marcelino Ramos/RS and to evaluate it, as a bio-indicator of environmental quality. The material was collected from November/1999 to December/2000, using three Malaise traps, with this distribution: point 1 (degrading area), point 2 (native wood area), and point 3 (gallery forest). 2442 specimens were colected, and an distributed into 23 subfamilies, which Microgastrinae and Rogadinae were the most representative ones. Glyptapanteles, Apanteles and Diolcogaster were the most abundant genera of Microgastrinae, while Aleiodes and Stiropius were the most abundant of Rogadinae. Index of diversity and equitability were used to discuss the richness of Microgastrinae and Rogadinae subfamilies and genera at the three points of collection. Point 3 (gallery forest) was the one which presented the biggest richness and the highest value regarding the level of equitability, as for the subfamilies, as for the genera of Microgastrinae, and point 2 presented the smallest value. Also for Rogadinae, point 3 showed the most abundant fauna; however, the richness was the same in the three points; the value of equitability was highest at the point 1 and slowest at the point 2. The flying activity of Braconidae belonging to the 23 subfamilies was studied at the three points. The peak to the captured coinobiontes occurrence was in December/1999 in all the three points. The peak for the idiobiontes was in April/2000 at the point 1, and in December/1999 and January/2000 at the points 2 and 3, respectively. In order to verify the similarity standard among the collection points, an analysis of grouping was performed, where it was possible to notice that points 1 and 2 presented a higher similarity. Point 3 stands out from the others, because it presents good conditions of original species recovering and it was the point with bigger abundance every month, mostly in spring and summer. Because of better regeneration conditions, this point possibly houses a richer collection of host insects. After the analysis of climatic variables, it can be said that temperature and humidity had influence on the presence of Braconidae in the Conservation Unity Teixeira Soares. Thus, it can be concluded that the community of Braconidae is much more significant in the mentioned CU, and they can be considered as important elements within the insect species of natural areas, because besides maintaining the dynamic equilibrium of ecosystems where they occur, they are bio-indicators of their preservation degree.
Keywords: Inseto; Himenoptero; Parasitóides; Braconidae; Diversidade biológica; Rio Grande do Sul; CIENCIAS BIOLOGICAS::ECOLOGIA